Genetic Dissection of the Type VI Secretion System in Acinetobacter and Identification of a Novel Peptidoglycan Hydrolase, TagX, Required for Its Biogenesis - Brent S. Weber (American Society for Microbiology, 2016)
ABSTRACT The type VI secretion system (T6SS) is a widespread secretory apparatus produced by Gram-negative bacteria that has emerged as a potent mediator of antibacterial activity during interbacterial interactions. Most Acinetobacter species produce a genetically conserved T6SS, although the expression and functionality of this system vary among different strains. Some pathogenic Acinetobacter baumannii strains activate this secretion system via the spontaneous loss of a plasmid carrying T6SS repressors. In this work, we compared the expression of T6SS-related genes via transcriptome sequencing and differential proteomics in cells with and without the plasmid. This approach, together with the mutational analysis of the T6SS clusters, led to the determination of the genetic components required to elaborate a functional T6SS in the nosocomial pathogen A. baumannii and the nonpathogen A. baylyi. By constructing a comprehensive combination of mutants with changes in the T6SS-associated vgrG genes, we delineated their relative contributions to T6SS function. We further determined the importance of two effectors, including an effector-immunity pair, for antibacterial activity. Our genetic analysis led to the identification of an essential membrane-associated structural component named TagX, which we have characterized as a peptidoglycan hydrolase possessing l,d-endopeptidase activity. TagX shows homology to known bacteriophage l,d-endopeptidases and is conserved in the T6SS clusters of several bacterial species. We propose that TagX is the first identified enzyme that fulfills the important role of enabling the transit of T6SS machinery across the peptidoglycan layer of the T6SS-producing bacterium. IMPORTANCE Acinetobacter baumannii is one of the most troublesome and least investigated multidrug-resistant bacterial pathogens. We have previously shown that A. baumannii employs a T6SS to eliminate competing bacteria. Here we provide a comprehensive analysis of the components of the T6SS of Acinetobacter, and our results provide genetic and functional insights into the Acinetobacter T6SS. Through this analysis, we identified a novel peptidoglycan hydrolase, TagX, that is required for biogenesis of the T6SS apparatus. This is the first peptidoglycanase specialized in T6SS function identified in any species. We propose that this enzyme is required for the spatially and temporally regulated digestion of peptidoglycan to allow assembly of the T6SS machinery.